2018
DOI: 10.1177/1534735418781736
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Preliminary Efficacy of a 10-Week Resistance and Aerobic Exercise Intervention During Neoadjuvant Chemoradiation Treatment in Rectal Cancer Patients

Abstract: Background: Neoadjuvant chemoradiation treatment (CRT) in rectal cancer patients is associated with a reduction in physical capacity, lean mass and increased fatigue. As a countermeasure to these treatment-related adverse effects, we examined the feasibility and preliminary efficacy of a 10-week exercise program during CRT. Methods: Ten rectal cancer patients (7 men, aged 27-70 years, body mass index = 26.4 ± 3.8 kg/m2) receiving CRT undertook supervised resistance and aerobic exercise twice weekly. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(106 citation statements)
references
References 43 publications
2
103
0
1
Order By: Relevance
“… 10 Recent evidence indicates that resistance exercise during neoadjuvant chemoradiation treatment is feasible in rectal cancer patients and promotes physical function. 11 In breast cancer patients undergoing adjuvant chemotherapy, resistance exercise alleviates physical fatigue and maintains QoL. 12 It has been demonstrated that the symptoms and physical condition of gastrointestinal cancer patients during palliative chemotherapy are enhanced by both resistance and aerobic exercise.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Recent evidence indicates that resistance exercise during neoadjuvant chemoradiation treatment is feasible in rectal cancer patients and promotes physical function. 11 In breast cancer patients undergoing adjuvant chemotherapy, resistance exercise alleviates physical fatigue and maintains QoL. 12 It has been demonstrated that the symptoms and physical condition of gastrointestinal cancer patients during palliative chemotherapy are enhanced by both resistance and aerobic exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Singh et al [8] reported that ten weeks of combined resistance and aerobic exercise during CRT were feasible and improved muscle strength in patients with rectal cancer. In contrast to our program, mainly machine supported resistance training was applied [8]. It seems reasonable to suppose, that machine supported training is more effective than a simple resistance band training.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant clinical effects of exercise interventions have been proven over all phases of the oncological treatment [7]. These exercise interventions were also feasible for patients undergoing CRT [8]. However, a limited period of time between diagnosis and resection usually leads to postpone exercise therapy to the postoperative period [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of neoadjuvant systemic chemotherapy is still under investigation [23][24][25] , during recruitment to the EMPOWER trial, University Hospital Southampton NHS Foundation Trust adopted systemic neoadjuvant chemotherapy prior to chemoradiotherapy as a standard treatment. This consisted of oxaliplatin 130 mg.m − 2 intravenously on day 1, oral capecitabine 1000 mg.m − 2 (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] given in a 3 weekly cycle x 4 cycles over 12 weeks, followed the 'standard' chemoradiotherapy programme as described above.…”
Section: Neoadjuvant Cancer Treatmentmentioning
confidence: 99%
“…The standard waiting period between completion of NCRT and surgery is generally at least 8 weeks 12 (or in some NHS hospitals up to 14 weeks) and therefore represents a unique opportunity to intervene with exercise prehabilitation. In this area of research, early evidence demonstrates the feasibility and preliminary effectiveness of exercise training (unimodal prehabilitation delivered in varied formats) for people with rectal cancer scheduled for NCRT and surgery [13][14][15][16][17][18][19] . To date, however, no exercise RCTs have been reported on both physical and psychological health measures in people with rectal cancer (although the EXERT trial is currently recruiting) 20 or indeed any patient group scheduled for a multimodal treatment pathway 21 .…”
Section: Introductionmentioning
confidence: 99%